Hemangioendotelioma epitelial: um tumor raro com apresentação atípica - Madalena Reis; Alcina Tavares; Luís Ferreira; Lina De Carvalho (Sociedade Galega de Medicina Interna, 2016)
Epithelioid Hemangioendothelioma is a rare neoplasia, and has its origin in the vascular endothelium. It may grow in several organs and tissues. There is not any approved therapeutic scheme and the prognosis is unpredictable. It is reported the case of a 54-year-old male patient, with the diagnosis of pulmonary epithelioid hemangioendothelioma, with atypical imaging and clinical presentation and multiple organ involvement at the time of the diagnosis. The patient did not start chemotherapy and died two months after the histological diagnosis. Due to the rarity of this neoplasia and the inexistence of approved therapeutic scheme, by reporting this case we intend to contribute to future clinical studies.